The Study on Recovery Vehicle Scheduling Problem of Industrial Waste Recycling - Fan, Hou Ming; Li, Jia Shu; Zhang, Xiao Nan (Applied Mechanics and Materials, 2012)
In recent years, china are paying attention to the development of the circular economy and the ecological industrial parks, industry, as the industry of the largest emissions of industrial waste, the circular economy is more concern by people. The recovery transport process of industrial waste recycling is the important part of the industrial circular economy, reasonable scheduling solution is the effective means to improve the recovery and processing speed of industrial wastes and make the cost of recycling lower. In this paper, through analysis and research the recovery transport links of industrial waste recycling, points out that the vehicle scheduling problem of industrial waste recycling is the scheduling problem combined full load with not-full load, and for this problem, build vehicle scheduling optimization model, use ant colony optimization algorithm to solve it, and that achieved good results.